2021
DOI: 10.5539/ibr.v14n5p40
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors that Influence Academics’ Knowledge Sharing Behaviour in Higher Education Institutions

Abstract: This study explores the organisational and individual factors that influence knowledge sharing behaviour among UK universities’ academics. Furthermore, the research also aims to provide recommendations on how knowledge sharing can be promoted. Few studies have been conducted to explore Knowledge Sharing behaviour in the context of higher education institutions. This research sheds light on the factors that influence knowledge sharing behaviour in higher learning institutions. Data for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The study also confirmed that adding the quality of services reflects the importance of the service as well as its support in the success of the information system. The study by Oqba & Najmuddin, (2011); Al Rushud, (2021), andChumg et al (2019) determined the impact of the information quality on the knowledge management of the customer in the communications institutions of Algeria. The researchers used the questionnaire and distributed it to workers, and these studies reached many conclusions, the imperative of which was that management of customer knowledge based on high-quality information achieved highly competitive advantage and had a positive impact on organizations.…”
Section: ) Completenessmentioning
confidence: 99%
“…The study also confirmed that adding the quality of services reflects the importance of the service as well as its support in the success of the information system. The study by Oqba & Najmuddin, (2011); Al Rushud, (2021), andChumg et al (2019) determined the impact of the information quality on the knowledge management of the customer in the communications institutions of Algeria. The researchers used the questionnaire and distributed it to workers, and these studies reached many conclusions, the imperative of which was that management of customer knowledge based on high-quality information achieved highly competitive advantage and had a positive impact on organizations.…”
Section: ) Completenessmentioning
confidence: 99%
“…From various studies, the ability of knowledge sharing students is influenced by multiple factors (Al Rushud, 2021). The first factor is the individual factor.…”
Section: Introductionmentioning
confidence: 99%